Antimicrobial efficacy of two mouthrinses against Candida albicans: An in vitro study - Nagappan Nagappan; Bharath Champakesan; Nagaland Tirupati; Thomson Maridasan D'cruz; Palanivel Pandian Ramasubramanian; Parvathy Premnath (Wolters Kluwer Medknow Publications, 2019)
Background: Mouthrinses have been used for centuries with the objective of reducing the amount of microorganisms in the oral cavity. Mouthrinses are used as adjuncts to mechanical oral hygiene. Therapeutic mouthwashes are often recommended as an adjunct to mechanical plaque control for prevention of plaque accumulation and to maintain gingival and periodontal health. Mechanical control alone for reducing recalcitrant biofilms in the oral cavity has been challenged because it is considered to be rather time-consuming and most importantly insufficient for effective oral hygiene. The aim of this study was to evaluate the antimicrobial efficacy of herbal and 0.2% chlorhexidine gluconate mouthrinse against Candida albicans. Materials and Methods: The minimum inhibitory concentration and antimicrobial effectiveness (zone of inhibition) of a herbal mouthrinse and 0.2% chlorhexidine mouthrinse were determined by broth macro-dilution and agar well diffusion method, respectively. Results: The zone of inhibition of C. albicans was 26mm for the 0.2% chlorhexidine mouthrinse, whereas it was 12mm for the Arowash liquid mouthrinse. Conclusion: Chlorhexidine mouthrinse (0.2%) has a better antimicrobial efficacy against the C. albicans when compared to herbal mouthrinse (Arowash liquid).